الصـورة الإستعارية في شعر (( حسن طه السنجاري )) - ALI , HAIDAR KHALIL; SULAYMAN, ISAM MUHAMMAD (Journal of Duhok University, 2023)
The research aims to shed light on the writer and poet (Hasan Taha Al-Sinjari) and his prolific production and in particular his poetic production. In addition to his Qur’anic writings and studies, and his books in the field of language, he has approximately fourteen collections of poetry. Since his prolific production of poetry requires a lot of research and studies because it contains many poetic arts and images, the research focused on the metaphorical image in his poetry, because it occupied an important and abundant aspect of his creative texts, in addition to his ability to formulate it in a distinct artistic way that excites a lot of imagination in the recipient’s mind. He also used verbal and declarative metaphors to enrich his texts and produce them in a way that is striking to the reader and to demonstrate the strength of his style and his skill in drawing his metaphorical images in a manner commensurate with the sophistication of his poetic talent . The research plan required that it consist of an introduction, a preface, two sections, and a conclusion in which we mentioned the most important conclusions that we reached. In the introduction, we talked about the importance of metaphor and its images in poetic art, while we divided the preface into two parts. The first: We mentioned an overview of the poet’s life, his professional career, and the works he published and his collections. The second: We designated it as a linguistic metaphor. As for the first section, we devoted it to talking about spatial metaphor and the personification and anthropomorphism it included in the poet’s poetry. We also devoted the second section to declarative metaphor and the personification and anthropomorphism it included for him .